Preparation method and application of high-dispersion PtCo alloy catalyst based on'pyrolysis etching-confinement pyrolysis' strategy
By adopting the ‘pyrolysis etching – limited-domain pyrolysis’ strategy in MOF materials, a highly dispersed ultra-small limited-domain PtCo nanoalloy catalyst is solved, and the problem of random combination of active sites in traditional pyrolysis strategies is achieved, achieving high-efficiency hydrogen evolution activity and electrochemical stability under acidic and alkaline conditions.
Patent Information
- Application Number
- CN202411714843.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-11
AI Technical Summary
In the traditional pyrolysis strategy of existing Pt-based alloy catalysts, the active sites are randomly combined and the HER active sites are unclear, resulting in insufficient catalytic activity and stability, making it difficult to achieve large-scale industrial production.
Using the ‘pyrolysis etching – limited-domain pyrolysis’ strategy, a highly dispersed ultra-small limited-domain PtCo nanoalloy catalyst was constructed by heat treatment, acid leaching and limited-domain pyrolysis in ZIF-67 derived carbon.
It has achieved strong hydrogen evolution activity and high electrochemical stability under both acidic and alkaline conditions, providing a research basis and universal construction strategy, and providing an innovative solution for the design of ultra-small limited-domain PtCo nano alloys.
Smart Images

Figure CN119793503A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and in particular relates to a preparation method and application of a highly dispersed PtCo alloy catalyst based on a 'pyrolysis etching-confined pyrolysis' strategy. Background Art
[0002] Hydrogen evolution by water electrolysis has attracted widespread attention as an effective way to generate and store clean energy using renewable energy. Among them, Pt-based catalysts are considered to be the most efficient catalyst type in the hydrogen evolution reaction (HER) under alkaline conditions. In order to improve the catalytic activity and utilization efficiency of Pt, Pt-based alloys have been widely used through coupling design with 3d transition metals. As a precursor of 3d transition metals, porous metal-organic frameworks (MOFs) show unique advantages in the preparation of efficient Pt-based alloys. The nitrogen atoms in MOFs can form chemical bonds with metal nanoparticles, further improving the catalytic performance.
[0003] The preparation strategy of Pt-based alloys is usually to load Pt-containing precursors on MOFs and perform in situ pyrolysis. For example, Pt and Co precursors are introduced into ZIF-8 and then pyrolyzed to construct PtCo alloys. There are also studies that introduce Pt organic ligands into MOF ligands and then pyrolyze them. However, these traditional in situ pyrolysis strategies often require complex interface structure regulation between MOF and Pt / Co precursors (such as the classic hard acid soft base principle), which makes it challenging to achieve large-scale synthesis of Pt-based alloys under mild conditions. In addition, the random combination process may lead to the burial of active sites or weakened interactions with the support. Although there are a few reports on ex situ pyrolysis, the confined environment of MOF-derived carbon has not been fully utilized. Therefore, it is particularly urgent to develop a simple and universal method for large-scale preparation of Pt-based alloy catalysts, especially a strategy suitable for industrial applications. Summary of the invention
[0004] In order to solve the problem that the traditional pyrolysis strategy of MOF materials leads to random combination of active sites and unclear HER active sites, the present invention proposes a "pyrolysis etching-confined pyrolysis" strategy. The preparation method and application of a highly dispersed PtCo alloy catalyst based on the 'pyrolysis etching-confined pyrolysis' strategy are used to construct a highly dispersed PtCo alloy, which is confined in a polyhedral porous carbon framework from ZIF-67. The prepared material has excellent electrocatalytic activity, providing a research basis and universal construction strategy for the design of ultra-small confined PtCo nanoalloys.
[0005] The present invention adopts the following technical solution: A method for preparing highly dispersed PtCo alloy catalysts based on the 'pyrolysis etching-confined pyrolysis' strategy. Initially, the catalysts were prepared by heating them at 900 °C in an Ar / H 2 ZIF-67 particles were simply heat-treated in a 95% / 5% (volume ratio) atmosphere to obtain ZIF-67-derived carbon containing large Co nanoparticles (denoted as Co LNP@ZIF-67-C). Subsequently, acid leaching was performed to remove accessible Co nanoparticles (NPs) to construct a porous framework with disordered Co nanoparticles or smaller clusters (Co SNP@ZIF-67-C). The pore size (about 1.16 nm) of ZIF-67 can be retained after pyrolysis. In addition, due to the removal of large Co nanoparticles, a large number of pore structures containing nitrogen coordination were generated during the etching process, which provided sites for capturing Pt. Therefore, by immersing CoSNP@ZIF-67-C in an aqueous solution of chloroplatinic acid hexahydrate, these pores can be used to capture free [PtCl 6 ] 2- ions (about 0.5 nm). It can be predicted that at 60°C, [PtCl 6 ] 2- The Pt cations in the cavities can be confined by the nitrogen tip through Pt-N coordination. Since disordered Co nanoparticles or clusters and Pt atoms coexist in the confined space, the Ar / H 2 PtCo@ZIF-67-C can be obtained by simple heat treatment in a 95% / 5% (volume ratio) atmosphere. 2 The presence of can not only help Co catalyze the growth of highly graphitized carbon and improve the conductivity of the catalyst material, but also confine the resulting PtCo alloy. In addition, the coexistence of Pt and Co species in the confined space is conducive to their coupling. This "pyrolysis etching-confined pyrolysis" strategy can avoid the complex regulation steps between MOF and precursor.
[0006] The specific steps are as follows: Synthesis of S1, Co LNP@ZIF-67-C and Co SNP@ZIF-67-C Synthesis of ZIF-67: 2-methylimidazole and Co(NO 3 ) 2 6H 2 O was dissolved in a mixed solution of methanol and ethanol, respectively. The two solutions were then mixed and stirred continuously for 10 s. The final solution was stored at room temperature for 20 h. The purple precipitate was collected by centrifugation, washed several times with ethanol, and dried at 60 °C to obtain the product ZIF-67. Then, in Ar / H 2ZIF-67 was carbonized at 900 °C in a carbon atmosphere. It was first heated from room temperature to 350 °C and kept at this temperature for 1.5 h. Then, it was heated to 900 °C and kept at this temperature for 3.5 h. The heating rate during the whole heating process was 2 °C min -1 , and cooled naturally to room temperature to obtain Co LNP@ZIF-67-C; The prepared Co LNP@ZIF-67-C was heated in H 2 SO 4 The solution was acid-washed, and after centrifugation, it was washed with deionized water until neutral, and Co SNP@ZIF-67-C (referring to Co LNP@ZIF-67-C containing mainly small Co particles) was obtained. The acid washing was to remove large Co particles, thereby leaving smaller Co particles with uniform particle size. Synthesis of S2, Co SNP-Pt SA@ZIF-67-C Co SNP@ZIF-67-C powder and chloroplatinic acid hexahydrate were added into ultrapure water, stirred in a water bath at 60 °C for 16.5 h, then centrifuged and vacuum dried to obtain Co SNP-Pt SA@ZIF-67-C. Synthesis of S3 and PtCo@ZIF-67-CX In Ar / H 2 The Co SNP-Pt SA@ZIF-67-C was heat treated at 600-900°C in an atmosphere to obtain a PtCo alloy, denoted as PtCo@ZIF-67-CX, where X represents the pyrolysis temperature.
[0007] Furthermore, in step S1, 2-methylimidazole, Co(NO 3 ) 2 6H 2 O, the dosage ratio of the mixed solution composed of methanol and ethanol is 1.97g:1.746g:40mL, wherein the volume ratio of methanol to ethanol is 1:1.
[0008] Furthermore, in step S2, the usage ratio of Co SNP@ZIF-67-C powder, chloroplatinic acid hexahydrate and ultrapure water is 100 mg: 1 mL: 10 mL, wherein the concentration of chloroplatinic acid hexahydrate is 0.02 g / mL.
[0009] Furthermore, the Ar / H 2 The volume ratio of Ar to H2 in the atmosphere is 95%:5%.
[0010] A highly dispersed PtCo alloy catalyst based on the 'pyrolysis etching-confined pyrolysis' strategy is applied to electrocatalytic hydrogen evolution under acidic and alkaline conditions.
[0011] The beneficial effects of the present invention are as follows: This paper proposes a "pyrolysis etching-confined pyrolysis" strategy to construct ZIF-67-derived carbon-confined PtCo nanoalloys for acidic and alkaline electrocatalytic hydrogen evolution: using etched ZIF-67-derived carbon as a precursor, using Pt-N coordination bonds and spatially confined Pt single atoms, regulating the pyrolysis temperature and atmosphere, and constructing highly dispersed ultra-small PtCo nanoalloy catalysts (about 2.5 nm). The catalyst exhibits strong hydrogen evolution activity and high electrochemical stability in both acidic and alkaline media. Combined with electrochemical performance testing, impedance kinetics analysis and explanation of the electrocatalytic hydrogen evolution mechanism provide a research basis and universal construction strategy for the design of ultra-small confined PtCo nanoalloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 TEM image of the precursor Co LNP@ZIF-67-C; Figure 2 TEM image of the precursor Co SNP@ZIF-67-C; Figure 3 TEM image of the precursor Co SNP-Pt SA@ZIF-67-C; Figure 4 TEM image of PtCo@ZIF-67-C-700; Figure 5 0.5 MH 2 SO 4 HER polarization curves and corresponding Tafel plots of PtCo@ZIF-67-C-700 (I), Co SNP-Pt SA@ZIF-67-C (II), CoSNP@ZIF-67-C (III), and Pt / C (IV); Figure 6 HER polarization curves and current density and corresponding Tafel curves of PtCo@ZIF-67-C (I), Co SNP-Pt SA@ZIF-67-C (II), Co SNP@ZIF-67-C (III) and Pt / C (IV) under 1 M KOH; Figure 7 0.5 MH 2 SO 4 HER polarization curves and current density of PtCo@ZIF-67-C-600 (I), PtCo@ZIF-67-C-700 (II), PtCo@ZIF-67-C-800 (III), and PtCo@ZIF-67-C-900 (IV) and the corresponding Tafel plots; Figure 8HER polarization curves and current density and corresponding Tafel curves of PtCo@ZIF-67-C-600 (I), PtCo@ZIF-67-C-700 (II), PtCo@ZIF-67-C-800 (III), and PtCo@ZIF-67-C-900 (IV) in 1 M KOH; Fig. 9 is the mass activity of PtCo@ZIF-67-C-700 (I) and Pt / C (IV) in acidic medium at an overpotential of 30 mV; Fig.10 Mass activity of PtCo@ZIF-67-C-700 (I) and Pt / C (IV) at an overpotential of 30 mV in alkaline media; Fig.11 It is a chronopotentiometry test under acidic conditions; Fig.12 Chronopotentiometry under alkaline conditions. DETAILED DESCRIPTION
[0013] The present invention is further described with reference to examples.
[0014] 1. Preparation of highly dispersed PtCo alloy catalyst (1) Synthesis of Co LNP@ZIF-67-C and Co SNP@ZIF-67-C Synthesis of ZIF-67: 2-Methylimidazole (1.97 g) and Co(NO 3 ) 2 6H 2 O (1.746 g) was dissolved in 40 mL of a mixed solution of methanol and ethanol (the volume ratio of methanol to ethanol was 1 / 1), and then the two solutions were stirred continuously for 10 s. The final solution was stored at room temperature for 20 h. The purple precipitate was collected by centrifugation, washed with ethanol several times, and dried at 60 °C to obtain the product ZIF-67. Subsequently, the product was heated to 40 °C under Ar / H 2 ZIF-67 was carbonized at 900 °C in a carbon atmosphere (volume ratio of 95% / 5%), first heated from room temperature to 350 °C and kept at this temperature for 1.5 h, then heated to 900 °C and kept at this temperature for 3.5 h. The heating rate during the whole heating process was 2 °C min -1 The prepared Co LNP@ZIF-67-C was cooled to room temperature naturally. 2 SO 4The solution was acid-washed for a certain period of time, and then washed with deionized water until neutral after centrifugation to obtain CoSNP@ZIF-67-C (referring to Co LNP@ZIF-67-C containing mainly small Co particles). The acid washing is to remove large Co particles, leaving smaller Co particles with uniform particle size.
[0015] The morphology of the precursor materials was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 It can be seen that the smooth rhombic polyhedral morphology of pure ZIF-67 is well preserved after heat treatment, but the surface becomes rough with larger particles. Figure 2 It can be seen that as the acid leaching treatment proceeds, most of the large Co particles are removed, resulting in a uniform distribution of small Co nanoparticles or clusters and a porous structure containing carbon defects and nitrogen-tipped cavities (denoted as Co SNP@ZIF-67-C).
[0016] (2) Synthesis of Co SNP-Pt SA@ZIF-67-C Co SNP@ZIF-67-C powder (100 mg) and chloroplatinic acid hexahydrate (1 mL, 0.02 g / mL) were added to ultrapure water (DI, 10 mL), stirred in a 60 °C water bath for 16.5 h, then centrifuged and vacuum dried to obtain Co SNP-Pt SA@ZIF-67-C. Figure 3 It can be seen that due to the Pt−N coordination and confinement effect, Co SNP@ZIF-67-C captures free [PtCl 6 ] 2- ions (about 0.5 nm), Co SNP-Pt SA@ZIF-67-C still maintains its original morphology, and uniform nanoparticles can be observed in the TEM images.
[0017] (3) Synthesis of PtCo@ZIF-67-CX In Ar / H 2 The Co SNP-Pt SA@ZIF-67-C was heat treated at different temperatures (600−900 °C) in a CO atmosphere (95% / 5% by volume) to obtain a PtCo alloy, denoted as PtCo@ZIF-67-CX, where X represents the pyrolysis temperature.
[0018] from Figure 4 It can be seen that due to the Co metal in Ar / H 2(5%) atmosphere, many protruding carbon nano-onions with amorphous cores were observed on the surface of PtCo@ZIF-67-C-700, which is conducive to the transfer of protons / electrons. At the same time, further observation revealed that the PtCo alloy was wrapped by a layer of interconnected onion-like carbon thick shell. From the elemental mapping of Pt and Co, the distribution of Pt and Co almost overlapped. It may be due to the fusion of Pt and Co in the confined space, which illustrates the importance of confined pyrolysis to control the interface structure. In addition, the PtCo alloy encapsulated by the onion-like carbon shell also helps to resist harsh and severe reaction conditions.
[0019] 2. HER electrochemical performance test under alkaline conditions The performance of electrochemical hydrogen evolution reaction (HER) was tested on a conventional three-electrode system of a CHI 760E electrochemical workstation. A catalyst-coated L-shaped glassy carbon electrode (3 mm in diameter) was used as the working electrode, Hg / HgO (alkaline medium) and Hg / Hg 2 Cl 2 (acidic medium) as the reference electrode, and graphite rod as the counter electrode. All polarization curves were corrected with 90% iR compensation to eliminate the ohmic drop on the electrolyte. 2.5 mg of catalyst powder and 5 μL of Nafion (20 wt%) were dispersed in 192 μL of deionized water and 48 μL of anhydrous ethanol and ultrasonicated for 1 h to form a uniform catalyst ink. 3.5 μL of the well-dispersed catalyst ink was dropped onto a pre-polished glassy carbon electrode (0.07 cm 2 ) and dried at room temperature for measurement, the catalyst loading was approximately 0.51 mg cm -2 The catalyst was tested by linear sweep voltammetry (LSV), Tafel slope, chronopotentiometry (CP) and electrochemical impedance spectroscopy (EIS) using an electrochemical workstation to evaluate its electrocatalytic performance.
[0020] First, the reference electrode was calibrated with a reversible hydrogen electrode (RHE) in high-purity H 2 Saturated 0.5 MH 2 SO 4 In the solution, two Pt foils were used as the working electrode and the counter electrode, respectively, and saturated calomel was used as the reference electrode. The potential range was -0.2 to -0.4 V at 2 mV s -1 Cyclic voltammetry (CV) was performed at a scan rate of 1.5 MH / s, and the average of the two potentials with zero current was taken as the thermodynamic potential of the hydrogen electrode reaction. 2 SO 4 The CV results for the RHE calibration of mercury / mercuric oxide can be described as E ( vs. RHE) = E ( vs. Saturated calomel) +0.262 V. In 1 M KOH solution, with 0.5 MH 2 SO 4 In contrast, the RHE calibrated CV results for mercury / mercury oxide in 1 M KOH can be described as E ( vs. RHE) = E ( vs. Mercury / mercury oxide) +0.922 V.
[0021] The three-electrode system was then placed at 0.5 MH 2 SO 4 The LSV experiments were carried out in 1 M KOH solution with a potential range of -0.15 to -0.42 V and -0.85 to -1.2 V, respectively, and a scan rate of 5 mV s -1 , the Tafel slope is determined by plotting the current density versus the logarithm of the overpotential (log |j|).
[0022] The EIS performance was measured in the frequency range of 0.01 Hz to 100 kHz. The CP experiment was performed at 0.0007 A (i.e. 10 mAcm -2 The solution resistance R can be obtained through the impedance spectrum. s , then use E = E RHE − 90%iR s To correct the LSV curve for liquid resistance. vs. The impedance test is carried out under RHE potential. The solution resistance R can be obtained through the impedance spectrum. s , then use E = E RHE − 90%iR s To perform liquid resistance correction on the LSV curve.
[0023] 3. Electrocatalytic hydrogen evolution test: The synthesized PtCo@ZIF-67-CX catalyst was evenly coated on a platinum carbon electrode to prepare a working electrode for electrochemical testing. Then, an electrochemical workstation was used to measure the hydrogen evolution reaction (HER) activity of the sample under alkaline conditions in a three-electrode system. LSV, EIS and CV tests were performed in sequence according to the same electrochemical test method as above. According to the R obtained in EIS s The LSV curves were corrected for liquid resistance and the electrochemical active surface area of the material was calculated.
[0024] By performing multiple impedance tests on the samples, it can be obtained that the average solution resistance of the catalyst in acidic and alkaline electrolytes is 7.5 Ω and 8.5 Ω, respectively. Based on this result, the LSV curve is corrected for liquid resistance.
[0025] Figure 5 and Figure 6 The electrochemical performance of PtCo@ZIF-67-C-700 and the precursor was tested, and the results showed that PtCo@ZIF-67-C had the lowest overpotential and lowest Tafel slope under both acidic and alkaline conditions. This shows that alloying can induce strong electronic interaction between Pt and Co, effectively increasing the rate of hydrogen evolution reaction and further improving HER performance.
[0026] Figure 7 and Figure 8 The hydrogen evolution performance of materials prepared at different pyrolysis temperatures was investigated. The alloy temperature was optimized and it was found that the catalyst prepared at an alloy temperature of 700 °C had the best HER performance.
[0027] Fig. 9 and Fig.10 It is shown that the catalytic efficiency and mass activity of PtCo@ZIF-67-C-700 are higher than those of Pt / C in both acidic and alkaline media, which indicates that the catalytic efficiency of each Pt active site is high in both acidic and alkaline media.
[0028] Fig.11 and Fig.12 The stability of the PtCo@ZIF-67-C-700 catalyst was also investigated. Under acidic conditions, the chronopotentiometry (CP, 10 mA cm) of PtCo@ZIF-67-C-700 was significantly higher than that of commercial Pt / C. -2 , 0.5 MH 2 SO 4 ) showed a durability of 24 hours, while Pt / C was only stable for about 4 hours before a significant drop in overpotential occurred. This may be due to the fact that the PtCo nanoalloy is completely encapsulated in the graphite carbon shell through the coordination confinement effect, so the reactants cannot access them, which strongly proves that the catalyst has excellent stability in acidic media. Similarly, PtCo@ZIF-67-C also has good stability under alkaline conditions.
[0029] Based on the above test results, it can be seen that the highly dispersed PtCo alloy catalyst constructed by the present invention exhibits excellent electrocatalytic HER activity and stability under acidic and alkaline conditions. This catalyst not only effectively improves the rate of hydrogen evolution reaction through the strong electronic interaction between Pt and Co, but also exhibits a lower Tafel slope, further proving its efficient catalytic performance in alkaline media. In short, this study provides a general strategy for constructing highly dispersed metal alloy catalysts using MOF precursors, and provides an effective way to improve the efficiency of alkaline electrocatalytic HER, which has potential application prospects.
[0030] In this paper, a "pyrolysis etching-confined pyrolysis" strategy is proposed, through which a highly dispersed PtCo nanoalloy catalyst confined in ZIF-67-derived carbon is constructed. The catalyst exhibits strong hydrogen evolution activity and high electrochemical stability in both acidic and alkaline media. In the pyrolysis process, the appropriate pyrolysis temperature H 2 The presence of can not only help Co catalyze the growth of highly graphitized carbon and improve the conductivity of the catalyst material, but also confine the resulting PtCo alloy, enhance the electron transfer between Pt and Co, and improve the electrocatalytic performance. Compared with the existing technology, the improvement in alkaline HER performance of this material is mainly attributed to the construction of confined ultrafine PtCo alloy. By precisely regulating the electronic synergy between Pt and Co, the material exhibits higher electrocatalytic activity, better stability and durability. This innovative design provides a new direction for the development of efficient electrocatalysts in the future.
[0031] The above-mentioned implementation mode is only used to illustrate the content of the present invention, but it is not a limitation of the present invention. Relevant technical personnel in this field can also make corresponding adjustments and modifications without departing from the scope of the present invention. Therefore, all technical solutions formed by equivalent replacement or equivalent modification belong to the protection scope of the present invention.
Claims
1. A method for preparing a highly dispersed PtCo alloy catalyst based on the strategy of 'pyrolysis etching-confined pyrolysis', characterized in that: A "pyrolysis etching-confined pyrolysis" strategy is proposed to construct a highly dispersed PtCo alloy confined in a polyhedral porous carbon framework from ZIF-67. First, nitrogen-containing porous cavities and disordered and uniform Co particles / clusters are generated by pyrolysis etching of ZIF-67. Then, Pt atoms are spatially confined by Pt-N coordination and narrow pores inherited from ZIF-67. Subsequently, a highly dispersed PtCo alloy catalyst confined in the polyhedral porous carbon framework of ZIF-67 is prepared by adjusting the alloy temperature and atmosphere.
2. The method for preparing a highly dispersed PtCo alloy catalyst based on the strategy of 'pyrolysis etching-confined pyrolysis' according to claim 1, characterized in that: The steps include: Synthesis of S1, Co LNP@ZIF-67-C and Co SNP@ZIF-67-C Synthesis of ZIF-67: 2-methylimidazole and Co(NO3)2·6H2O were dissolved in a mixed solution of methanol and ethanol, respectively. The two solutions were then mixed and stirred continuously for 10 s. The final solution was stored at room temperature for 20 h. The purple precipitate was collected by centrifugation, washed several times with ethanol, and dried at 60 °C to obtain the product ZIF-67. Subsequently, ZIF-67 was carbonized at 900 °C in an Ar / H2 atmosphere. It was first heated from room temperature to 350 °C and kept at this temperature for 1.5 h, and then heated to 900 °C and kept at this temperature for 3.5 h. The heating rate during the whole heating process was 2 °C min -1 , and naturally cooled to room temperature to obtain Co LNP@ZIF-67-C; The prepared Co LNP@ZIF-67-C was acid-washed in H2SO4 solution, centrifuged and washed with deionized water until neutral, to obtain Co SNP@ZIF-67-C (referring to Co LNP@ZIF-67-C mainly containing small Co particles). The acid washing was to remove large Co particles, leaving smaller Co particles with uniform particle size. Synthesis of S2, Co SNP-Pt SA@ZIF-67-C Co SNP@ZIF-67-C powder and chloroplatinic acid hexahydrate were added into ultrapure water, stirred in a water bath at 60 °C for 16.5 h, then centrifuged and vacuum dried to obtain Co SNP-Pt SA@ZIF-67-C. Synthesis of S3 and PtCo@ZIF-67-CX Co SNP-Pt SA@ZIF-67-C was heat treated at 600-900 °C in an Ar / H2 atmosphere to obtain a PtCo alloy, denoted as PtCo@ZIF-67-CX, where X represents the pyrolysis temperature.
3. The method for preparing a highly dispersed PtCo alloy catalyst based on the 'pyrolysis etching-confined pyrolysis' strategy according to claim 2, characterized in that: In step S1, the dosage ratio of the mixed solution consisting of 2-methylimidazole, Co(NO3)2·6H2O, methanol and ethanol is 1.97 g:1.746 g:40 mL, wherein the volume ratio of methanol to ethanol is 1:
1.
4. The method for preparing a highly dispersed PtCo alloy catalyst based on the 'pyrolysis etching-confined pyrolysis' strategy according to claim 2, characterized in that: In step S2, the usage ratio of Co SNP@ZIF-67-C powder, chloroplatinic acid hexahydrate and ultrapure water is 100 mg: 1 mL: 10 mL, wherein the concentration of chloroplatinic acid hexahydrate is 0.02 g / mL.
5. The method for preparing a highly dispersed PtCo alloy catalyst based on the 'pyrolysis etching-confined pyrolysis' strategy according to claim 2, characterized in that: The volume ratio of Ar to H2 in the Ar / H2 atmosphere is 95%:5%.
6. A PtCo alloy catalyst prepared by the preparation method according to claim 1 is used for electrocatalytic hydrogen evolution under acidic and alkaline conditions.
Citation Information
Patent Citations
Method for preparing transition metal Mo-based materials of different sizes through precise confinement path and application of transition metal Mo-based materials
CN115805093A
Cited By
Composite catalyst for hydrogen evolution of anion exchange membrane electrolytic cell and preparation method of composite catalyst
CN120575241A
In-situ etching-micro-crystallization treatment carbon carrier supported catalyst and preparation method thereof
CN122348209A